A Common Brotherhood for Their Mutual Benefit: Sir Charles Macara and Internationalism in the Cotton Industry, 1904–1914. (21st September 2015) - ROBINS, JONATHAN E.
Abstract : Unlike their national counterparts, international trade associations are a little-studied aspect of the global economic system. Much of the literature on trade associations has focused on rent-seeking behavior, although theories of transaction costs and social capital have been gaining influence. This article uses the early history of the International Federation of Master Cotton Spinners' and Manufacturers' Associations (IFMCSMA), still operating today as the International Textile Manufacturers' Federation, to test different explanations for the formation and persistence of international trade associations. The IFMCSMA case illustrates the challenges of rent-seeking on an international scale, and highlights the importance of social ties in building cooperation. Firms and individuals used the IFMCSMA to pursue reforms across the cotton textile industry and enjoyed some success in collective negotiations with other actors and organizations.